Developing a career in conservation medicine. (13th July 2013) - Meredith, Anna
Abstract : The University of Edinburgh's online distance learning programme in conservation medicine leads to the award of a masters degree, a diploma or a certificate. Programme director Anna Meredith describes who the course is aimed at and what is on offer